Recent Advances in the Preparation and Application of Organic–inorganic Hybrid Magnetic Nanocatalysts on Multicomponent Reactions - Bodaghifard, Mohammad A.; Hamidinasab, Mahdia; Ahadi, Najmieh (Current Organic Chemistry, 2018)
The combination of advantages of multicomponent reactions (MCRs) and magnetic nano catalysts is going to be an emerging and strategic area and is an ideal blend for the development of sustainable methodologies in organic synthesis in green and benign media. This review focuses on the synthesis, functionalization, and application of organic-inorganic hybrid magnetic nanoparticles as novel task-specific catalysts on multicomponent reactions (MCRs) in recent years. So, properly magnetic nanoparticles can be used as building blocks for the fabrication of various functional moieties, and their application in catalysis of MCRs will be briefly reviewed. The heterogenization of the catalyst using magnetic nanoparticles allows it to be recovered and reused using an external magnet. The approach to magnetic separation is not only easy, cost-effective, favorable for work-up procedures and industrial applications, but also is usually more effective than filtration or centrifugation as it diminishes the loss of the catalyst.
Keywords: hybrid materials